Exploring the Mediating Role of Multiple Organ Dysfunction in Sepsis-Induced Disseminated Intravascular Coagulation and Its Impact on Worsening Prognosis - Guangjie Wang MD; Chenxiao Hao MD; Sun Yao MD; Yiqin Wang PHD; Zongtao Xu MD; Huiying Zhao MD; Youzhong An MD (Clinical and Applied Thrombosis/Hemostasis)
Disseminated intravascular coagulation (DIC) poses a high mortality risk, yet its exact impact remains contentious. This study investigates DIC's association with mortality in individuals with sepsis, emphasizing multiple organ function. Using data from the Peking University People's Hospital Investigation on Sepsis-Induced Coagulopathy database, we categorized patients into DIC and non-DIC groups based on DIC scores within 24 h of ICU admission (< 5 cutoff). ICU mortality was the main outcome. Initial data comparison preceded logistic regression analysis of mortality factors post-propensity score matching (PSM). Employing mediation analysis estimated direct and indirect associations. Of 549 participants, 131 were in the DIC group, with the remaining 418 in the non-DIC group. Following baseline characteristic presentation, PSM was conducted, revealing significantly higher nonplatelet sequential organ failure assessment (nonplt-SOFA) scores (6.3 ± 2.7 vs 5.0 ± 2.5, P < 0.001) and in-hospital mortality rates (47.3% vs 29.5%, P = 0.003) in the DIC group. A significant correlation between DIC and in-hospital mortality persisted (OR 2.15, 95% CI 1.29–3.59, P = 0.003), with nonplt-SOFA scores (OR 1.16, 95% CI 1.05-1.28, P = 0.004) and hemorrhage (OR 2.33, 95% CI 1.08-5.03, P = 0.032) as predictors. The overall effect size was 0.1786 (95% CI 0.0542-0.2886), comprising a direct effect size of 0.1423 (95% CI 0.0153-0.2551) and an indirect effect size of 0.0363 (95% CI 0.0034-0.0739), with approximately 20.3% of effects mediated. These findings underscore DIC's association with increased mortality risk in patients with sepsis, urging anticoagulation focus over bleeding management, with organ dysfunction assessment recommended for anticoagulant treatment efficacy.